2014
DOI: 10.1038/cr.2014.130
|View full text |Cite
|
Sign up to set email alerts
|

Honeysuckle-encoded atypical microRNA2911 directly targets influenza A viruses

Abstract: Influenza A viruses (IAVs), particularly H1N1, H5N1 and H7N9, pose a substantial threat to public health worldwide. Here, we report that MIR2911, a honeysuckle (HS)-encoded atypical microRNA, directly targets IAVs with a broad spectrum. MIR2911 is highly stable in HS decoction, and continuous drinking or gavage feeding of HS decoction leads to a significant elevation of the MIR2911 level in mouse peripheral blood and lung. Bioinformatics prediction and a luciferase reporter assay showed that MIR2911 could targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
400
2
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(423 citation statements)
references
References 23 publications
13
400
2
8
Order By: Relevance
“…Several labs have used PCR to note the absence of individual plant miRNAs that were abundant in a given source before ingestion [27][28][29]; however, our sequencing data as well as others have observed that the plant miRNAs that are taken up after consumption are not necessarily those that are most abundant in the plant (Supplementary information, Table S1) [21,22]. Therefore, there is likely a selective mechanism for the uptake of specific plant miRNAs in mammals.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Several labs have used PCR to note the absence of individual plant miRNAs that were abundant in a given source before ingestion [27][28][29]; however, our sequencing data as well as others have observed that the plant miRNAs that are taken up after consumption are not necessarily those that are most abundant in the plant (Supplementary information, Table S1) [21,22]. Therefore, there is likely a selective mechanism for the uptake of specific plant miRNAs in mammals.…”
Section: Discussionmentioning
confidence: 70%
“…However, it has been argued that the inability to detect the uptake of plant miRNAs was due to only looking at a few selected miRNAs rather than using sequencing to screen for all plant miRNAs. Furthermore, the cross-kingdom presence and potential function of plant miRNAs in mammals are supported by independent studies from only two different labs in the past three years, highlighting the need for further verification [22,[34][35][36].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…121,122 A recent study revealed that the long-known beneficial effect of honeysuckle decoction (Lonicera japonica) traditionally used in Chinese medicine against flu might imply miRNA. A rRNA-derivedatypical miRNA, miR-2911 has been identified that is resistant to boiling and can reach an adequate amount in the honeysuckle decoction.…”
Section: Treatment Potential For Xeno-mirnasmentioning
confidence: 99%
“…Nonetheless, controversy remains. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] The possibility of cross-kingdom regulation of gene expression via ingested miRNAs could be of particular interest in the mutualistic relationships of plants and their pollinators. The relationship involves an exchange of nutrients for the reproduction-enabling service of pollination, but is complicated by the antagonistic relationship of the two players, which is characterized by a fundamental conflict of interest.…”
Section: Introductionmentioning
confidence: 99%